Frequency of Hepatotoxicity in Pulmonary Tuberculosis Patients Taking Anti-Tuberculous Therapy - liaqat, Muhammad Bilal; Batool , Huma; Haider , Afaq; Atif, Ahmad; Iqbal, Asifa; Mujahid, Abdul Majid (Indus Journal of Bioscience Research, 2025)
Background: Anti-tuberculous therapy (ATT), while effective in treating pulmonary tuberculosis, carries the risk of hepatotoxicity due to drugs such as isoniazid, rifampicin, and pyrazinamide. Objective: To determine the frequency of hepatotoxicity among patients with newly diagnosed pulmonary tuberculosis receiving standard ATT during the intensive phase. Methods: This cross-sectional study was conducted at the Department of Pulmonology, Allama Iqbal Medical College / Jinnah Hospital, Lahore. A total of 112 patients aged 18–75 years with newly diagnosed pulmonary tuberculosis on ATT for at least one month were enrolled using non-probability consecutive sampling. Patients with a history of liver disease, prior tuberculosis, alcohol use, hakeem medications, or drug hypersensitivity were excluded. Liver function tests (ALT, AST, ALP, bilirubin) were performed fortnightly. Results: Among 112 patients, 9 (8.0%) developed ATT-induced hepatotoxicity. Most cases were observed within 4 to 6 weeks of treatment. A significant association was found between hepatotoxicity and age over 50 years (p = 0.04) and smoking history (p = 0.01). Other factors such as gender, residence, weight, and income level did not show statistically significant associations. ALT was elevated in all affected cases, followed by raised AST, ALP, and bilirubin levels. Most patients recovered with dose modification; one required hospitalization. Conclusion: It is concluded that hepatotoxicity is a notable adverse effect during the intensive phase of anti-tuberculous therapy, with smoking and older age emerging as significant risk factors.